Análisis, desarrollo e implementación de un sistema hidropónico ebb and flow automatizado para la fundación Ecosur-Ecuador - Porras Pumalema, Cristian Daniel (2021)
In this research project, an automated EBB and FLOW hydroponic system was designed and implemented at EcoSur-Riobamba foundation. It started with the evaluation and the planning of the objectives to reach in this research project. Through the applicative, experimental, explanatory research, and descriptive and experimental research methods, a prototype device was developed and built, integrated by electronic devices TFT screen3,5 ' 'with a graphical interface in Python 3.6.5 - Tkinter module, Raspberry Pi 4 from Arduino Uno. These devices control the temperature, humidity (DHT11), UV radiation (ML8511), pH sensors and a x8 relay module to activate actuators. The system generates a database (SQlite3) of the environmental and chemical climatic variables, it also has a VNC server for connection from remote devices via Wifi for real-time monitoring and control of the mentioned variables. The problem and the objectives of the Investigation are in the First Chapter. The Theoretical Foundation is systematically summarized in the Second Chapter. In the Third and Fourth Chapters, Methodological Research is developed. The results was a quantitative validation of the Implemented Prototype, Through a descriptive statistical analysis of the population for Black Seed Simpson Lettuces. Comparing them between those that were grown through EBB and FLOW cultivation and those grown outside in the open sky. Finally, in the Fifth Chapter, the conclusions and recommendations of the research work are discussed.